Mampukah Proses Produksi Perusahaan Besar Industri Besi dan Baja Dasar di Indonesia Mencapai Tingkat Efisiensi Maksimal? - Azizah, Salsabila Nur; Budiasih, Budiasih (Seminar Nasional Official Statistics, 2023)
Basic iron and steel (ISIC 24101) is one of the important commodities in the development process in Indonesia and its use in the construction sector reaches more than 75 percent. However, Indonesia still imports to fulfill domestic consumption. The production process is suspected to be inefficient. The purpose of this study is to identify the presence or absence of technical inefficiency in the basic iron and steel production process and its determinants using secondary data from the results of the 2017 Annual Survey of Manufacturing Industry Companies with the unit of analysis being large companies, and the Stochastic Frontier Analysis approach. The results show that the production process of basic iron and steel in Indonesia is not yet efficient. The majority of large companies have a medium level of efficiency. Companies that operate for a full year tend to be inefficient in their production process activities. On the other hand, large companies will also tend to be inefficient in their production process if they do not carry out R&D activities and do not innovate their products.